Lightest weight-class athletes are at higher risk of weight regain: results from the French-Rapid Weight Loss Questionnaire - Pélissier, L.; Ennequin, G.; Bagot, S.; Pereira, B.; Lachèze, T.; Duclos, M.; Thivel, D.; Miles-Chan, J.; Isacco, L. (The Physician and Sportsmedicine, 2023)
Context Rapid weight loss (RWL) is a common precompetitive strategy used by athletes in weight-class sports and carries with it an increased risk to future cardiometabolic health. The Rapid Weight Loss Questionnaire (RWLQ) is a self-reported tool designed to identify and characterize such weight loss practices.